Exploration and Practice of Maker Education Mode in Innovation and Entrepreneurship Education - Yang, Yan (Frontiers in Psychology, 2020)
This study was conducted with the purpose of exploring the impact of positive entrepreneurial psychological quality in innovation and entrepreneurship education, as well as the development of maker education in colleges and universities. The questionnaire survey method – The Positive Mental Characters Scale for Chinese College Students – and the SPSS 26.0 mathematical statistical analysis software were adopted to analyze and characterize the development of innovation and entrepreneurship education in colleges and universities, as well as the practice of maker education. The results show that there are differences in the factors that affect the positive entrepreneurial psychological quality of college students studying different majors in the liberal arts and sciences. Family economy has the most obvious impact on liberal arts students, sports activities have the most obvious impact on science students, has and grades have the most obvious impact on engineering students; the average score of college students’ innovation and entrepreneurship ability is around 3.0, showing that the overall innovation and creativity ability is general. Furthermore, there are differences in the development of the maker education model between the eastern and western universities. Overall, the maker faculty of eastern universities are more complete, with a larger number of professors, associate seniors, and intermediate teachers. In addition, the investigation on the positive entrepreneurial psychological quality shows a positive effect on cultivating students’ healthy entrepreneurial quality as well as promoting the development and practice of maker education.